The Relationship Between P-Wave Velocity and Slake Durability Index - Hosseini, Mehdi (International Journal of Geography and Geology, 2015)
Many manmade structures such as tunnels, roads, bridges, dams, power plants, etc. have been built either on top or inside rocks. Therefore, it is highly crucial to determine the various parameters of rocks in construction designs. Slake durability index is one of the widely applied features in this respect. A great deal of time and money is required to prepare samples and conducts slake durability tests. For that reason, easier and less expensive methods are employed to determine slake durability index. This research project mainly attempted to propose an equation to estimate the slake durability index after the second cycle (Id2) based on the speed of sound (VP). In addition to the longitudinal wave velocity test and the Brazilian slake durability test, the point load was specified on the samples so as to further expand the study. The tests were conducted on samples of sandstone, tuffite, andesite, red sandstone, limestone, marl, marble and travertine. The simple regression yielded three separate equations, i.e. the first relationship between the slake durability index of the second cycle and velocity of longitudinal waves, the second relationship between slake durability index of the second cycle and tensile strength and the third relationship between the slake durability index of the second cycle and the point load index. The results demonstrated that the greatest coefficient of determination (R2) was in the relationship between the slake durability index of the second cycle and the velocity of longitudinal waves. The results of comparison between this relationship and those proposed by other researchers suggested that the equation offered in this paper can accurately estimate the slake durability index in a broad range of rocks.